Well-posedness of mixed problems for multidimensional hyperbolic equations with wave operator - Aldashev, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We establish the unique solvability and obtain the explicit expression for the classical solution of the mixed problem formultidimensional hyperbolic equations with wave operator.